Teologi Tahajjud Pemikiran Prof. Dr. Moh. Sholeh Melawan Mitos Sangkal di Kalangan Masyarakat Kabupaten Sumenep Madura - Zaitur Rahem (LP2M STIT Palapa Nusantara, 2017)
The community formed by the trappings of culture. The birth of a sense of cultural initiative, creativity, and initiative of human social life. Each community in various regions has its own culture. All of theIT formed over social accumulation, Bohemian flavor, and the results kesepakata together. Depth on creating, meruwat, and caring culture in Indonesian society is very strong. On the island of Madura, a sense of belonging to that culture is still strong. Including culture believing in things that are myths. This study will reveal the myths deny reality in the Madurese community. With qualitatively method, researchers will collect data from a number of sources. Data collection will be done with the snowball sampling technique. All information obtained from informants become authoritative data in terms of writing this review. of the research, found that refute the myth has no empirical basis. Deny only be born of anxiety Madurese community. Solutions address the threat to deny the myth is Denen taqarruban ilallah through prayer tahajud media. Salah tahajud alternative enjadi soothe the soul and maintain the stability of functioning organs become more finally.